Religious Broadcasting Compliance in West Java: An Analysis of Regulatory Dynamics and Violations - Roni Tabroni; Adiyana Slamet; Syintia Nurfitria; Naditha Rizkya Hantoro; Amin Shabana (Communicatus: Jurnal Ilmu komunikasi, 2026)
The growing presence of religious content in broadcasting media has intensified concerns over regulatory compliance, particularly in regions with many religious broadcasting institutions. As Indonesia's province with the most broadcasting institutions, West Java offers a relevant context for examining compliance among religious broadcasters. This study analyzes patterns of compliance, forms of violation, and regulatory interventions concerning religious broadcasting in West Java from 2021 to 2024. Using a qualitative case study design, data were collected through document analysis, observation, interviews, KPID West Java monitoring reports, violation records, and regulatory documents, with participants and sources purposively selected and data analyzed thematically, validated through triangulation. Findings show that of 476 broadcasting institutions in West Java, 32 adopted religious formats, comprising two television and thirty radio stations. Violations were concentrated in 2021-2022, including discriminatory policies, inaccurate broadcasts, unbalanced reporting, and content with potential to incite social conflict. In response, KPID West Java strengthened enforcement through written warnings, clarification, partner collaboration, and Circular Letter No. 1 of 2022 on religious broadcasting content. Following these interventions, no violations were recorded in 2023, with only one case in 2024, underscoring the role of sustained supervision and multi-stakeholder collaboration in strengthening compliance within Indonesia's pluralistic media environment.